2015
DOI: 10.1111/cei.12678
|View full text |Cite
|
Sign up to set email alerts
|

Collectin liver 1 and collectin kidney 1 and other complement-associated pattern recognition molecules in systemic lupus erythematosus

Abstract: SummaryThe objective of this study was to explore the involvement of collectin liver 1 (CL-L1) and collectin kidney 1 (CL-K1) and other pattern recognition molecules (PRMs) of the lectin pathway of the complement system in a cross-sectional cohort of systemic lupus erythematosus (SLE) patients. Concentrations in plasma of CL-L1, CL-K1, mannan-binding lectin (MBL), M-ficolin, H-ficolin and L-ficolin were determined in 58 patients with SLE and 65 healthy controls using time-resolved immunoflourometric assays. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
3
26
1
Order By: Relevance
“…The LP proteins are synthesized predominantly by the liver [34]; however, it has been described that H-ficolin is abundant in lung tissue [35], that M-ficolin is produced primarily by leucocytes [28] and that CL-K1 is also produced by kidney cells [36]. We confirmed that CL-L1 and CL-K1 concentrations correlate strongly, as we have reported previously [37]. These proteins have been found to exist primarily as heteromeric complexes in the circulation [4].…”
Section: Discussionsupporting
confidence: 89%
“…The LP proteins are synthesized predominantly by the liver [34]; however, it has been described that H-ficolin is abundant in lung tissue [35], that M-ficolin is produced primarily by leucocytes [28] and that CL-K1 is also produced by kidney cells [36]. We confirmed that CL-L1 and CL-K1 concentrations correlate strongly, as we have reported previously [37]. These proteins have been found to exist primarily as heteromeric complexes in the circulation [4].…”
Section: Discussionsupporting
confidence: 89%
“…Chinese hamster ovary (CHO) cells co‐transfected with both proteins were observed to synthesize such complexes with the same CL‐10:CL‐11 ratio. Finally, studies show that CL‐10 and CL‐11 serum levels are highly correlated, which further supports the idea of naturally occurring heteromeric CL‐10/11 (CL‐L/K) complexes . Until recently, human CL‐10 was considered as a cytoplasmic protein retained within the hepatocytes .…”
Section: Collectin‐10 and Collectin‐11supporting
confidence: 56%
“…Until recently, human CL‐10 was considered as a cytoplasmic protein retained within the hepatocytes . Nevertheless, CL‐10 on its own has now been defined as a serum protein with a median concentration of around 0.3 μg/ml (0.2–0.51 μg/ml) . How much of the CL‐10 content in serum that is a part of the CL‐10/11 heteromeric complex is still unknown.…”
Section: Collectin‐10 and Collectin‐11mentioning
confidence: 99%
“…The LPP patterns reported in SLE and RA differ from that found in our axSpA cohort. This possibly reflects that different parts of the innate immune system are involved in each of these diseases and might be due to that both SLE and RA are humoral‐associated autoimmune diseases, where autoantibodies precede the clinical presentation of the disease.…”
Section: Discussioncontrasting
confidence: 99%